ANALISIS KESEJAHTERAAN PSIKOLOGIS SEBAGAI FAKTOR PENENTU KESEHATAN MENTAL PADA KARYAWAN INDUSTRI MANUFAKATUR PT. S - Amatullah, Afiffah Rifdah; Hazim, Hazim (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study analyzes the role of Psychological Well-Being (PWB) in determining the mental health of employees in the manufacturing industry. Using a quantitative method and a survey of 100 production employees at PT. X, Pasuruan, East Java, this study employs the WEMWBS and GHQ-12 instruments. The results of the Pearson correlation test show a significant negative relationship between PWB and mental health (r= -0.218, p= 0.028), which means that the higher the psychological well-being, the lower the symptoms of mental disorders. Regression analysis shows that PWB contributes 4.7% to the variability of mental health, with a significant regression model (F = 4.981, p = 0.028), although the strength of the relationship is weak. These findings emphasize the importance of a work environment that supports psychological well-being, such as employee wellness programs, good management-employee communication, and work-life balance policies. This research recommends further studies with additional variables and more complex analytical methods for a more comprehensive understanding.